1996
DOI: 10.1080/00288330.1996.9516731
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical‐genetic variation in a wild and a cultured population of the greenshell mussel,Perna canaliculus

Abstract: A wild and a cultured greenshell mussel (Perna canaliculus) population were compared for biochemical genetic variation at seven polymorphic and four monomorphic allozyme loci. Significant heterozygote deficiencies were observed for all polymorphic loci Lap,2, Pgi, and Pgm) for both populations (except the Pgi locus of the wild mussel population). Genotypic disequilibrium was calculated for both populations: genotypic frequencies were significantly nonrandom at three pairs of loci among the wild mussels, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Beaumont (1994) showed that PGM* and PGI* are not linked in M. edulis. Non-linkage of these two loci was also observed in mussels by Gardner et al (1996), and thus the two loci PGI* and PGM* make independent contributions to the identification of different groups of blue mussels.…”
Section: Discussionmentioning
confidence: 95%
“…Beaumont (1994) showed that PGM* and PGI* are not linked in M. edulis. Non-linkage of these two loci was also observed in mussels by Gardner et al (1996), and thus the two loci PGI* and PGM* make independent contributions to the identification of different groups of blue mussels.…”
Section: Discussionmentioning
confidence: 95%
“…Since the 1980s, mussel aquaculture in the study region has used large quantities of wild seed mussels transported from northern New Zealand to facilitate aquaculture expansion that was not possible from seeding with the insufficient locally caught wild seed supply (Dawber 2004). Northern mussels come from a different environment (Ren et al 2019), are genetically distinct from wild mussel populations in the study areas (Gardner et al 1996, Apte et al 2003, and have a different breeding periodicity (Alfaro et al 2001(Alfaro et al , 2003. One or more of these differences may result in an inability of the cultured mussels derived from imported northern seedstock to effectively contribute to larval supply in this non-natal region.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest surveys of population genetic structure in Perna canaliculus employed allozymes (biochemical markers) and reported partial isolation between northern and southern populations at about 38° S (Smith 1988), or an isolation-by-distance population structure (Gardner et al 1996). A subsequent and far larger allozyme survey found no evidence for either the north-south split or the isolation-by-distance results of earlier studies (Apte & Gardner 2001).…”
Section: Genetic Markersmentioning
confidence: 96%